Risk assessment of black soldier fly (Hermetia illucens (L.), Diptera: Stratiomyidae) larvae composting for circular waste management in southern Benin - Ogbon, E.A.; Dzepe, D.; Lalander, C.; Wiklicky, V.; Sinda, P.V.K.; Adeoti, R.; Mignouna, D.; Gbaguidi, B.; Behanzin, J.G.; Riggi, L.; Djouaka, R. (Walter de Gruyter GmbH, 2025)
Insect farming is becoming an important business in West Africa, and the black soldier fly (Hermetia illucens (L.), Diptera: Stratiomyidae) is one of the most widely farmed species. In this study, we investigated the potential risk factors, including heavy metals and pesticides, of the implementation of black soldier fly (BSF)-based technology for circular waste management in the context of Benin. The study was performed in two phases. In Phase 1, we identified and estimated the primary sources of biowaste streams suitable for BSF rearing in Benin. The study involved identifying these sources, estimating their availability, and analysing their characteristics, particularly in terms of contamination levels. In Phase 2, each identified biowaste streams was subjected to BSF larvae treatment and the levels of identified contaminants was analysed before and after the treatment, as well as some microbial contaminants such as Salmonella spp. and Escherichia coli and yeasts and moulds. The majority of biowaste streams and derived BSF larvae were contaminated with copper, chromium, cadmium, lead, and zinc. However, the concentrations detected were below the standard limit values recommended for animal feed. Traces of pesticides were detected in all biowaste streams and derived frass. No pesticide contamination was detected in BSF larvae. Salmonella spp. was found to be the most predominant pathogenic microorganism in fresh BSF larvae as well as in the frass. We therefore recommended to sanitiInsect farming is becoming an important business in West Africa, and the black soldier fly (Hermetia illucens (L.), Diptera: Stratiomyidae) is one of the most widely farmed species. In this study, we investigated the potential risk factors, including heavy metals and pesticides, of the implementation of black soldier fly (BSF)-based technology for circular waste management in the context of Benin. The study was performed in two phases. In Phase 1, we identified and estimated the primary sources of biowaste streams suitable for BSF rearing in Benin. The study involved identifying these sources, estimating their availability, and analysing their characteristics, particularly in terms of contamination levels. In Phase 2, each identified biowaste streams was subjected to BSF larvae treatment and the levels of identified contaminants was analysed before and after the treatment, as well as some microbial contaminants such as Salmonella spp. and Escherichia coli and yeasts and moulds. The majority of biowaste streams and derived BSF larvae were contaminated with copper, chromium, cadmium, lead, and zinc. However, the concentrations detected were below the standard limit values recommended for animal feed. Traces of pesticides were detected in all biowaste streams and derived frass. No pesticide contamination was detected in BSF larvae. Salmonella spp. was found to be the most predominant pathogenic microorganism in fresh BSF larvae as well as in the frass. We therefore recommended to sanitise all BSF larvae that are intended for use in animal feed. As was demonstrated in this study, no Salmonella spp. was found in the sanitised larvae. The findings of this study will promote the establishment of safety measures in the BSF farming sector.se all BSF larvae that are intended for use in animal feed. As was demonstrated in this study, no Salmonella spp. was found in the sanitised larvae. The findings of this study will promote the establishment of safety measures in the BSF farming sector.